THE APPLICATION OF CONTEXTUAL TEACHING AND LEARNING STRATEGIES IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT THE VOCATIONAL SCHOOL OF BINA TARUNA 1 IN MEDAN CITY - Wardati, Laila; Lubis, Masruroh; Nasution, Leni Masnidar; YM, Khairuddin; Hanafiah, Muhammad Ali (The Islamic Education and Multiculturalism Foundation, 2022)
This study aims to determine student learning outcomes using Contextual Teaching and Learning (CTL) learning strategies at vocational school of Bina Taruna Medan city and what are the challenges in implementing contextual teaching and learning strategies in improving student learning outcomes at vocational school of Bina Taruna Kota Medan. This research method is a qualitative research with a case study approach, the results of observations show that the application of contextual teaching and learning (CTL) learning strategies improves student learning outcomes. The improvement of student learning outcomes reflects the enthusiasm of students in taking lessons in class and is carried over to the test results of Islamic religious education subjects. The learning outcomes of Islamic religious education subjects are said to be classically complete.